A framework for real-time disinfection plan assembling for a contamination event in water distribution systems. (1st May 2020) - Qiu, Mengning; Salomons, Elad; Ostfeld, Avi
Abstract: Water distribution system contamination events caused by intentional, negligent, or accidental intrusion of biological, chemical, or radioactive contaminants have significant impacts on the health of the populations that it services. Therefore, it is important to have an effective plan that can be readily implemented to minimize the impact of these contamination events. However, limited research has been focused on strategic planning of the decontamination process of the contaminated infrastructure. This paper proposed a framework for assembling a disinfection plan in real-time by (1) partitioning a WDS into a number of district metered areas (DMAs), (2) generating a solution region for each of the DMAs, and (3) assemble an effective decontamination plan using solution region generated. This framework has been applied to three contamination events. The results show that, when planning for the decontamination stage of a contamination event, the use of the proposed framework can (1) significantly reduce the response time, (2) improve the quality of the decontamination plan, and (3) provide a model for optimizing the resource allocation. Graphical abstract: Image 1 Highlights: A framework for planning water distribution system decontamination is introduced. A decontamination plan can be readily assembled in real-time. Resources can be allocated dynamically subject to objectives and constraints. Decontamination can be planned to be performed in parallel, serially, or hybridly.